Effect of Paint Exposure Among Paint Workers and DNA Damage: A Scoping Review - Saironi, Afiqah; Awang, Normah; Ithnin, Anuar; Kamaluddin, Nurul Farahana; Ibrahim, Farah Wahida; Chan, Kok Meng (Malaysian Journal of Medicine and Health Sciences, 2023)
Paint contains various complex chemical mixtures, such as aliphatic hydrocarbons, aromatic hydrocarbons (primarily toluene), ketones, and benzene as reported at previous studies. Toxicity from some chemicals can cause early DNA damage with various factors. A scoping review was conducted via literature review on relevant studies on the effect of paint exposure on paint workers and DNA damage. A systematic search was conducted in October 2021 via PubMed, Scopus, and Web of Science databases. The key terms used were paint, solvent-based paint, organic solvent, mixed organic solvent, occupational exposure and DNA damage, oxidative stress, genotoxicity on a painter, paint worker. From 561 articles, only 13 articles were finally selected based on the inclusion, exclusion criteria, and eligibility criteria. The literature showed that biomonitoring studies on painters were consistently reporting positive and significant DNA damage due to exposure to different types of compounds mixed in a paint. However, there were fewer studies on paint manufacturing factory workers compared to painters while paint manufacturing workers exposed various chemical everyday during the paint production which potentially susceptible to occupational toxicity. In conclusion, this review suggests that exposure to paints could induce early DNA damage among paint workers and further investigations on paint exposure among paint manufacturing factory workers and the DNA damage were needed in order to improve occupational health among paint workers in the future.